Stainless steel seamless pipe and its manufacturing method

JP7626229B2Active Publication Date: 2025-02-04JFE STEEL CORP
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
JP2023537203
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2022-07-05
Filing Date
2023-03-08
Publication Date
2025-02-04
Estimated Expiration
2043-03-08

AI Technical Summary

Benefits of technology

【0032】 本発明によれば、降伏強さ:758MPa(110ksi)以上という高強度と、優れた低温靭性および耐食性とを兼ね備えたステンレス継目無鋼管を得ることができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007626229000001
    Figure 0007626229000001
  • Figure 0007626229000002
    Figure 0007626229000002
  • Figure 0007626229000003
    Figure 0007626229000003
Patent Text Reader

Abstract

Provided is a seamless stainless steel pipe having high strength, excellent low-temperature toughness, and corrosion resistance. This seamless stainless steel pipe has a specific component composition and contains, by volume percentage, at least 30% martensite phase, no more than 50% ferrite phase, and no more than 40% residual austenite phase. The pipe has a yield strength of 758 MPa or greater and a Charpy absorbed energy at -10°C, vE-10, of 40 J or greater.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a stainless steel seamless pipe suitable for use in oil wells and gas wells (hereinafter simply referred to as oil wells). The present invention relates to a stainless steel seamless pipe suitable for use in oil wells and gas wells (hereinafter simply referred to as oil wells). - This invention relates to stainless steel seamless pipes with improved corrosion resistance in severe high-temperature corrosive environments including those containing hydrogen sulfide (H2S) and in environments containing hydrogen sulfide (H2S). [Background technology]

[0002] Stainless steel seamless pipes are widely used for applications such as oil well pipes. In addition to excellent yield strength, oil well pipes are also required to have excellent low-temperature toughness in line with the recent development of oil fields in cold regions.

[0003] Furthermore, in view of the expected depletion of energy resources in the near future, active development is being carried out for oil wells in severe corrosive environments, such as deep oil fields, environments containing carbon dioxide gas, and sour environments containing hydrogen sulfide, which have not been considered in the past. Therefore, steel pipes for oil wells are required to have high corrosion resistance.

[0004] Conventionally, CO2 and Cl - In oil and gas fields, which are exposed to environments including the above, 13Cr martensitic stainless steel pipes have been commonly used as oil well pipes for mining. However, in recent years, the development of oil wells with even higher temperatures (up to 200°C) has progressed, and the corrosion resistance of 13Cr martensitic stainless steel pipes has sometimes been insufficient. Therefore, there is a demand for oil well steel pipes with even higher corrosion resistance that can be used in such environments.

[0005] In response to such demands, for example, Patent Document 1 proposes a stainless steel for oil wells containing, by mass%, C: 0.05% or less, Si: 1.0% or less, Mn: 0.01 to 1.0%, P: 0.05% or less, S: less than 0.002%, Cr: 16 to 18%, Mo: 1.8 to 3%, Cu: 1.0 to 3.5%, Ni: 3.0 to 5.5%, Co: 0.01 to 1.0%, Al: 0.001 to 0.1%, O: 0.05% or less, and N: 0.05% or less, with Cr, Ni, Mo, and Cu satisfying specific relationships.

[0006] Patent Document 2 proposes a high-strength stainless steel seamless pipe for oil wells containing, by mass%, C: 0.005-0.05%, Si: 0.05-0.50%, Mn: 0.20-1.80%, P: 0.030% or less, S: 0.005% or less, Cr: 12.0-17.0%, Ni: 4.0-7.0%, Mo: 0.5-3.0%, Al: 0.005-0.10%, V: 0.005-0.20%, Co: 0.01-1.0%, N: 0.005-0.15%, and O: 0.010% or less, in which Cr, Ni, Mo, Cu, C, Si, Mn, and N satisfy specific relationships.

[0007] In addition, Patent Document 3 describes the following composition by mass: C: 0.05% or less, Si: 0.5% or less, Mn: 0.15 to 1.0%, P: 0.030% or less, S: 0.005% or less, Cr: 14.5 to 17.5%, Ni: 3.0 to 6.0%, Mo: 2.7 to 5.0%, Cu: 0.3 to 4.0%, W: 0.1 to 2.5%, V: 0.02 to 0.20%, Al: 0.10% or less, N: 0.15% The following high-strength stainless steel seamless pipe for oil wells has been proposed, which contains 0.0005-0.0100% B, has a composition in which C, Si, Mn, Cr, Ni, Mo, Cu, N, and W satisfy specific relationships, and further has a structure containing, by volume ratio, more than 45% martensite phase as the main phase, 10-45% ferrite phase as the second phase, and 30% or less retained austenite phase. As a result, it has a yield strength of 862 MPa or more, and is free of CO2, Cl2, and - It is said that this will result in a high-strength stainless steel seamless pipe for oil wells that exhibits sufficient corrosion resistance even in high-temperature, severely corrosive environments that contain H2S.

[0008] Patent Document 4 proposes a high-strength stainless steel seamless pipe for oil wells, which contains, by mass%, C: 0.06% or less, Si: 1.0% or less, P: 0.05% or less, S: 0.005% or less, Cr: more than 15.7% and not more than 18.0%, Mo: 1.8% to 3.5%, Cu: 1.5% to 3.5%, Ni: 2.5% to 6.0%, Al: 0.10% or less, N: 0.10% or less, O: 0.010% or less, W: 0.5% to 2.0%, and Co: 0.01% to 1.5%. In this case, C, Si, Mn, Cr, Ni, Mo, Cu, and N satisfy specific relationships, and further has a structure containing, by volume, 25% or more of martensite phase, 65% or less of ferrite phase, and 40% or less of retained austenite phase. This provides a yield strength of 758 MPa or more and is also resistant to CO2 and Cl. - It is said that this will result in a high-strength stainless steel seamless pipe for oil wells that exhibits sufficient corrosion resistance even in high-temperature, severely corrosive environments that contain H2S.

[0009] Patent Document 5 proposes a high-strength stainless steel seamless pipe for oil wells, which contains, by mass%, C: 0.06% or less, Si: 1.0% or less, Mn: 0.01% or more and 1.0% or less, P: 0.05% or less, S: 0.005% or less, Cr: 15.2% or more and 18.5% or less, Mo: 1.5% or more and 4.3% or less, Cu: 1.1% or more and 3.5% or less, Ni: 3.0% or more and 6.5% or less, Al: 0.10% or less, N: 0.10% or less, O: 0.010% or less, and Sn: 0.001% or more and 1.000% or less, in which C, Si, Mn, Cr, Ni, Mo, Cu, and N have a composition that satisfies a specific relationship, and further has a structure that contains, by volume fraction, 30% or more of martensite phase, 65% or less of ferrite phase, and 40% or less of retained austenite phase. This provides a yield strength of 758 MPa or more and is also resistant to CO2 and Cl. - It is said that the company has been able to obtain high-strength stainless steel seamless pipes for oil wells that exhibit sufficient corrosion resistance even in high-temperature, severely corrosive environments, including those containing uranium.

[0010] Patent Document 6 proposes a high-strength stainless steel seamless pipe for oil wells, which contains, by mass%, C: 0.06% or less, Si: 1.0% or less, Mn: 0.01% or more and 1.0% or less, P: 0.05% or less, S: 0.005% or less, Cr: 15.2% or more and 18.5% or less, Mo: 1.5% or more and 4.3% or less, Cu: 1.1% or more and 3.5% or less, Ni: 3.0% or more and 6.5% or less, Al: 0.10% or less, N: 0.10% or less, O: 0.010% or less, and Sb: 0.001% or more and 1.000% or less, in which C, Si, Mn, Cr, Ni, Mo, Cu, and N have a composition that satisfies a specific relationship, and further has a structure that contains, by volume fraction, 30% or more of martensite phase, 65% or less of ferrite phase, and 40% or less of retained austenite phase. This provides a yield strength of 758 MPa or more and is also resistant to CO2 and Cl. - It is said that this will result in a high-strength stainless steel seamless pipe for oil wells that exhibits sufficient corrosion resistance even in high-temperature, severely corrosive environments that contain H2S. [Prior art documents] [Patent documents]

[0011] [Patent Document 1] International Publication No. 2013 / 146046 [Patent Document 2] International Publication No. 2017 / 168874 [Patent Document 3] International Publication No. 2018 / 155041 [Patent Document 4] International Publication No. 2021 / 065263 [Patent Document 5] International Publication No. 2021 / 187330 [Patent Document 6] International Publication No. 2021 / 187331 Summary of the Invention [Problem to be solved by the invention]

[0012] According to the conventional techniques proposed in Patent Documents 1 to 6, it is possible to improve the corrosion resistance of stainless steel, but the performance is still insufficient.

[0013] That is, as described above, oil well steel pipes are required to have high corrosion resistance capable of withstanding use in severe corrosive environments, in addition to excellent yield strength and low-temperature toughness.

[0014] For example, steel pipes for oil wells are required to have excellent resistance to corrosion in a carbon dioxide gas environment (CO2 corrosion resistance), and are particularly required to have excellent CO2 corrosion resistance even in high temperature environments.

[0015] In addition, steel pipes for oil wells are required to have the property of not causing sulfide stress cracking (SSC) in a hydrogen sulfide environment (SSC resistance). In particular, in the case of offshore oil fields, the specific gravity of cold seawater is high and it remains near the seabed, so the oil well pipes are exposed to temperatures lower than the atmospheric temperature in that area. Therefore, steel pipes for oil wells are required to have excellent SSC resistance even in low-temperature environments.

[0016] Furthermore, when extracting oil, there are cases where the properties (mainly permeability) of the layer (reservoir) in which the oil is stored are poor, resulting in insufficient production, or where the expected production volume cannot be obtained due to clogging in the reservoir. As a method to improve productivity, acidizing is sometimes performed by injecting an acid such as hydrochloric acid into the reservoir. For this reason, oil well steel pipes are also required to have excellent corrosion resistance in acid environments.

[0017] However, conventional technology has not yet produced steel pipes that have sufficient yield strength, low-temperature toughness, carbon dioxide corrosion resistance at high temperatures, SSC resistance at low temperatures, and corrosion resistance in acid environments.

[0018] In particular, the technology described in Patent Document 6 is said to provide high strength, corrosion resistance at high temperatures, and corrosion resistance in acid environments, but the sulfide stress cracking resistance was not necessarily sufficient. The reasons for this are thought to be as follows. That is, if the phase fraction during steel pipe manufacturing is not appropriate, hot workability becomes insufficient, and cracks and fractures occur on the inner and outer surfaces of the steel pipe. When such a steel pipe is used in an oil well, corrosive ions are retained inside the cracks and further concentrated as corrosion progresses, resulting in insufficient SSC resistance.

[0019] The present invention aims to solve such problems of the conventional technology and to provide a stainless steel seamless pipe that combines high strength, such as a yield strength of 758 MPa (110 ksi) or more, with excellent low-temperature toughness and corrosion resistance.

[0020] In the present invention, "excellent corrosion resistance" refers to excellent resistance to carbon dioxide gas corrosion at high temperatures, excellent SSC resistance at low temperatures, and excellent corrosion resistance in acid environments.

[0021] Here, "excellent carbon dioxide corrosion resistance at high temperatures" means that the corrosion rate when a test piece is immersed in a test liquid held in an autoclave: a 20 mass % NaCl aqueous solution (liquid temperature: 200°C, CO2 gas atmosphere at 30 atmospheres) for 336 hours is 0.127 mm / y or less.

[0022] In addition, "excellent SSC resistance at low temperatures" means that no cracks are observed in the test specimen after immersing a C-shaped test piece conforming to NACE TM0177 Method C in a 0.165 mass% NaCl aqueous solution (liquid temperature: 7°C, CO2 gas at 0.995 atm, H2S atmosphere at 0.005 atm) adjusted to pH 3.0 by adding acetic acid + sodium acetate for 720 hours and applying a load stress of 100% of the yield stress.

[0023] "Excellent corrosion resistance in an acid environment" means that the corrosion rate when a test piece is immersed in a 15 mass % hydrochloric acid solution heated to 80°C for 40 minutes is 600 mm / y or less.

[0024] "Low temperature toughness" refers to the Charpy absorbed energy vE -10 The Charpy absorbed energy vE -10 is measured according to the following procedure. First, in accordance with the provisions of ASTM E23, three V-notch test specimens (10 mm thick) are taken from each stainless steel seamless pipe, in which the longitudinal direction of the test specimen is perpendicular to the pipe axis and the notch is on a plane perpendicular to the pipe axis. Next, using these test specimens, a Charpy impact test is performed at a test temperature of -10°C, and the minimum absorbed energy of the three test specimens is determined as the Charpy absorbed energy vE at -10°C. -10 Let us assume that.

[0025] In order to achieve the above object, the present inventors have conducted extensive research into various factors that affect the corrosion resistance of stainless steels, particularly SSC resistance and corrosion resistance in acid environments. As a result, they have found that excellent corrosion resistance can be obtained by containing at least predetermined amounts of Cr, Mo, Sn, Co, and Ca, and by limiting the amount of Ni, which affects the phase fraction of the steel, to a predetermined range.

[0026] The present invention was completed based on these findings and further investigations.

[0027] 1. In mass percent, C: 0.06% or less, Si: 1.0% or less, Mn: 0.01% or more and 1.0% or less, P: 0.05% or less, S: 0.005% or less, Cr: 15.2% or more and 18.0% or less, Mo: 1.5% or more and 4.3% or less, Cu: 1.2% or more and 3.5% or less, Ni: 3.5% or more and 5.2% or less, V: 0.5% or less, Al: 0.10% or less, N: 0.10% or less, O: 0.010% or less, Sn: 0.001% or more and 1.000% or less Co: 0.01% to 1.00%; and Ca: 0.001% or more and 0.030% or less; The balance is Fe and unavoidable impurities. In terms of volume ratio, Martensite phase is 30% or more, Ferrite phase is 50% or less, and The retained austenite phase is 40% or less, Yield strength is 758MPa or more, Charpy absorbed energy vE at -10℃ -10 Stainless steel seamless pipe with a hardness of 40J or more.

[0028] 2. The composition of the components is, in mass%, Nb: 0.07% or less, Ti: 0.2% or less, W: 0.5% or less, B: 0.01% or less, Ta: 0.3% or less, Zr: 0.3% or less, REM: 0.3% or less, Mg: 0.01% or less, and Sb: 1.0% or less 2. The stainless steel seamless pipe according to 1 above, further comprising at least one selected from the group consisting of:

[0029] 3. Volume ratio, Martensite phase is 50% or more, Ferrite phase is 50% or less, and The retained austenite phase is 25% or less, 3. The stainless steel seamless pipe according to claim 1 or 2, having a yield strength of 862 MPa or more.

[0030] 4. A seamless steel pipe is manufactured from a steel material having the composition described in 1 or 2 above, The seamless steel pipe is heated to a quenching temperature of 850 to 1150°C, The seamless steel pipe after the heating is cooled at a cooling rate of 0.01°C / s or more to a cooling stop temperature of 50°C or less, The seamless steel pipe after cooling is heated to a tempering temperature of 500 to 650°C, In terms of volume ratio, Martensite phase is 30% or more, Ferrite phase is 50% or less, and The retained austenite phase is 40% or less, Yield strength is 758MPa or more, Charpy absorbed energy vE at -10℃ -10 A method for manufacturing a stainless steel seamless pipe, comprising the steps of: manufacturing a stainless steel seamless pipe having a hardness of 40J or more.

[0031] 5. Volume ratio, Martensite phase is 50% or more, Ferrite phase is 50% or less, and The retained austenite phase is 25% or less, 5. A method for producing a stainless steel seamless pipe as described above in 4, wherein the stainless steel seamless pipe has a yield strength of 862 MPa or more. Effect of the Invention

[0032] According to the present invention, it is possible to obtain a stainless steel seamless pipe which has a high strength of at least 758 MPa (110 ksi) yield strength, and which also has excellent low-temperature toughness and corrosion resistance. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0033] The present invention will be described in detail below.

[0034] [Component composition] The stainless steel seamless pipe of the present invention has the above-mentioned composition. First, the reasons for limiting the above-mentioned composition will be explained. Hereinafter, unless otherwise specified, "mass %" will be simply represented as "%".

[0035] C: 0.06% or less C is an element that is inevitably contained in the steelmaking process. If the C content exceeds 0.06%, the corrosion resistance decreases. For this reason, the C content is set to 0.06% or less. The C content is preferably 0.05% or less, more preferably 0.04% or less, and even more preferably 0.03% or less. On the other hand, from the viewpoint of corrosion resistance, the lower the C content, the better, so the lower limit of the C content is not particularly limited. However, from the viewpoint of decarburization costs, the C content is preferably 0.002% or more, more preferably 0.003% or more, and even more preferably 0.005% or more.

[0036] Si: 1.0% or less Si is an element that acts as a deoxidizer. However, if the Si content exceeds 1.0%, the hot workability and corrosion resistance are reduced. Therefore, the Si content is set to 1.0% or less, preferably 0.7% or less, more preferably 0.5% or less, and even more preferably 0.4% or less. On the other hand, the lower limit of the Si content is not particularly limited, but from the viewpoint of enhancing the deoxidizing effect, the Si content is preferably set to 0.03% or more, more preferably 0.05% or more, and even more preferably 0.1% or more.

[0037] Mn: 0.01 to 1.0% Mn is an element that acts as a deoxidizer and desulfurizer and improves hot workability. In order to obtain the effect of the deoxidizer and desulfurizer and to improve strength, the Mn content is set to 0.01% or more, preferably 0.03% or more, more preferably 0.05% or more, and even more preferably 0.1% or more. On the other hand, even if the Mn content exceeds 1.0%, the effect is saturated. For this reason, the Mn content is set to 1.0% or less, preferably 0.8% or less, more preferably 0.6% or less, and even more preferably 0.4% or less.

[0038] P:0.05% or less P is an element that reduces carbon dioxide corrosion resistance and SSC resistance. In order to obtain the desired corrosion resistance, the P content is 0.05% or less, preferably 0.04% or less, and more preferably 0.03% or less. On the other hand, since it is preferable to reduce the P content as much as possible, the lower limit of the P content is not particularly limited and may be 0%. However, since excessive reduction leads to an increase in costs, from the viewpoint of cost, the P content is preferably 0.005% or more, and more preferably 0.010% or more.

[0039] S: 0.005% or less S is an element that significantly reduces hot workability and hinders stable operation of the hot pipe making process. In addition, S exists as sulfide-based inclusions in steel and reduces corrosion resistance. Therefore, the S content is 0.005% or less, preferably 0.004% or less, more preferably 0.003% or less, and further preferably 0.002% or less. On the other hand, since it is preferable to reduce the S content as much as possible, the lower limit of the S content is not particularly limited and may be 0%. However, excessive reduction leads to an increase in cost, so from the viewpoint of cost, the S content is preferably 0.0003% or more, and more preferably 0.0005% or more.

[0040] Cr: 15.2~18.0% Cr is an element that forms a protective film on the surface of the steel pipe and contributes to improving corrosion resistance. If the Cr content is less than 15.2%, the desired carbon dioxide corrosion resistance and sulfide stress cracking resistance cannot be ensured. Therefore, the Cr content is set to 15.2% or more, preferably 15.5% or more, more preferably 16.0% or more, and even more preferably 16.30% or more. On the other hand, if the Cr content exceeds 18.0%, the ferrite fraction becomes too high and the desired strength cannot be ensured. Therefore, the Cr content is set to 18.0% or less, preferably 17.5% or less, more preferably 17.2% or less, and even more preferably 17.0% or less.

[0041] Mo: 1.5-4.3% Mo stabilizes the protective film on the steel pipe surface and -It increases resistance to pitting corrosion due to low pH and low temperature, thereby improving corrosion resistance. To obtain the desired corrosion resistance, the Mo content is set to 1.5% or more, preferably 1.8% or more, more preferably 2.0% or more, and even more preferably 2.3% or more. On the other hand, if the Mo content exceeds 4.3%, the ferrite fraction becomes too high and the desired strength cannot be ensured. For this reason, the Mo content is set to 4.3% or less, preferably 4.0% or less, more preferably 3.5% or less, and even more preferably 3.0% or less.

[0042] Cu: 1.2-3.5% Cu has the effect of strengthening the protective film on the steel pipe surface and enhancing the carbon dioxide corrosion resistance and sulfide stress cracking resistance. In order to obtain the desired strength and corrosion resistance, especially the carbon dioxide corrosion resistance, the Cu content is set to 1.2% or more, preferably 1.8% or more, more preferably 2.0% or more, and even more preferably 2.3% or more. On the other hand, if the Cu content is too high, the hot workability of the steel is reduced, and external surface defects are generated during pipe making, and the desired sulfide stress cracking resistance cannot be obtained. Therefore, the Cu content is set to 3.5% or less, preferably 3.2% or less, more preferably 3.0% or less, and even more preferably 2.7% or less.

[0043] Ni: 3.5-5.2% Ni improves the low-temperature toughness of steel. In addition, Ni contributes to an increase in the austenite fraction, and therefore affects the hot workability during hot rolling. In order to obtain the desired toughness, the Ni-containing layer is set to 3.5% or more, preferably 3.8% or more, more preferably 4.0% or more, and even more preferably 4.3% or more. On the other hand, if the Ni content exceeds 5.2%, the austenite fraction becomes too high, and the hot workability of the steel decreases. As a result, defects are more likely to occur during hot rolling, and the desired sulfide stress cracking resistance may not be obtained. For this reason, the Ni content is set to 5.2% or less, preferably 5.0% or less.

[0044] V: 0.5% or less V is an element that increases strength without impairing toughness by forming carbonitrides. V also has the effect of improving corrosion resistance. This is because V preferentially forms carbonitrides, which prevents corrosion-resistant elements such as Cr from forming carbonitrides and reducing the effective amount of corrosion resistance. However, even if V is contained in an amount exceeding 0.5%, the effect is saturated. For this reason, the V content is set to 0.5% or less, preferably 0.2% or less, and more preferably 0.1% or less. On the other hand, the lower limit of the V content is not particularly limited, but is preferably set to 0.01% or more, and more preferably 0.03% or more.

[0045] Al: 0.10% or less Al is an element that acts as a deoxidizer. However, if the Al content exceeds 0.10%, the corrosion resistance decreases. Therefore, the Al content is set to 0.10% or less, preferably 0.07% or less, and more preferably 0.05% or less. On the other hand, the lower limit of the Al content is not particularly limited, but from the viewpoint of enhancing the deoxidizing effect, the Al content is preferably set to 0.005% or more, more preferably 0.01% or more, and even more preferably 0.015% or more.

[0046] N: 0.10% or less N is an element that is inevitably contained in the steelmaking process, but it also increases the strength of steel. However, if the N content exceeds 0.10%, the amount of nitrides formed becomes excessive, and the corrosion resistance decreases. For this reason, the N content is set to 0.10% or less, preferably 0.07% or less, more preferably 0.05% or less, and even more preferably 0.03% or less. On the other hand, although the lower limit of the N content is not particularly limited, an extreme reduction in the N content leads to an increase in the steelmaking cost. For this reason, the N content is preferably set to 0.002% or more, more preferably 0.003% or more, and even more preferably 0.005% or more.

[0047] O: 0.010% or less O (oxygen) exists as an oxide in steel and has an adverse effect on various properties. For this reason, in the present invention, it is desirable to reduce the O content as much as possible. In particular, if the O content exceeds 0.010%, the hot workability and corrosion resistance decrease. For this reason, the O content is set to 0.010% or less. However, excessive reduction leads to an increase in costs, so from the viewpoint of cost, the O content is preferably 0.00005% or more, and more preferably 0.001% or more.

[0048] Sn: 0.001 to 1.000% Sn is an element necessary for improving corrosion resistance in an acid environment. In order to obtain the desired corrosion resistance, the Sn content is set to 0.001% or more, preferably 0.003% or more, more preferably 0.005% or more, and even more preferably 0.010% or more. On the other hand, even if the Sn content exceeds 1.000%, the effect is saturated. Therefore, the Sn content is set to 1.000% or less, preferably 0.500% or less, more preferably 0.100% or less, and even more preferably 0.050% or less.

[0049] Co: 0.01 to 1.00% Co is an element that improves corrosion resistance. In order to obtain the desired corrosion resistance, the Co content is set to 0.01% or more, preferably 0.03% or more, and more preferably 0.05% or more. On the other hand, even if Co is contained in an amount exceeding 1.00%, the effect is saturated. Therefore, the Co content is set to 1.00% or less, preferably 0.50% or less, more preferably 0.30% or less, and further preferably 0.10% or less.

[0050] Ca: 0.001 to 0.030% Ca is an element that improves hot workability through morphology control of sulfides, and contributes to improving SSC resistance in steel pipes by suppressing the occurrence of defects during pipe making. In order to obtain the above effect, the Ca content is set to 0.001% or more, preferably 0.003% or more, more preferably 0.005% or more, more preferably more than 0.010%, even more preferably 0.012% or more, and most preferably 0.014% or more. On the other hand, even if the Ca content exceeds 0.030%, the effect is saturated and an effect commensurate with the content cannot be expected. Therefore, the Ca content is set to 0.030% or less, preferably 0.025% or less, and more preferably 0.020% or less.

[0051] A stainless steel seamless pipe according to one embodiment of the present invention has a composition containing the above components with the balance being Fe and unavoidable impurities.

[0052] In another embodiment of the present invention, the above-mentioned composition may further optionally contain at least one selected from the group consisting of Nb, Ti, W, B, Ta, Zr, REM, Mg, and Sb. Nb, Ti, W, B, Ta, Zr, REM, Mg, and Sb may be optionally contained, and the lower limit of the content may be 0%.

[0053] Nb: 0.07% or less Nb is an element that forms carbonitrides and further improves strength and corrosion resistance, and can be contained as necessary. However, since Nb carbonitrides tend to reduce low-temperature toughness, when Nb is added, the Nb content is set to 0.07% or less, preferably 0.03% or less, and more preferably 0.01% or less. On the other hand, the lower limit of the Nb content may be 0%, but from the viewpoint of enhancing the effect of adding Nb, the Nb content is preferably set to 0.001% or more.

[0054] Ti: 0.2% or less Ti is an element that further improves strength and corrosion resistance, and can be contained as necessary. However, if Ti is contained in an amount exceeding 0.2%, low-temperature toughness decreases. Therefore, when Ti is added, the Ti content is set to 0.2% or less, preferably 0.05% or less, and more preferably 0.01% or less. On the other hand, the lower limit of the Ti content may be 0%, but from the viewpoint of enhancing the effect of adding Ti, the Ti content is preferably set to 0.001% or more.

[0055] W: 0.5% or less W is an element that contributes to further improving the strength of steel and stabilizes the protective film on the steel pipe surface to further improve corrosion resistance. However, if W is contained in an amount exceeding 0.5%, low-temperature toughness decreases. For this reason, when W is added, the W content is set to 0.5% or less, preferably 0.3% or less, and more preferably 0.2% or less. On the other hand, the lower limit of the W content is not particularly limited and may be 0%, but is preferably set to 0.05% or more, and more preferably set to 0.1% or more.

[0056] B: 0.01% or less B is an element that contributes to improving hot workability and also has the effect of suppressing the occurrence of cracks and fractures during the pipe-making process. However, if the B content exceeds 0.01%, the low-temperature toughness decreases. Therefore, when B is added, the B content is set to 0.01% or less, preferably 0.007% or less, and more preferably 0.005% or less. On the other hand, the lower limit of the B content is not particularly limited and may be 0%, but is preferably set to 0.0005% or more, and more preferably set to 0.001% or more.

[0057] Ta: 0.3% or less Ta is an element that has the effect of further improving the strength and corrosion resistance, and can be contained as necessary. However, if it is contained in an amount exceeding 0.3%, the effect is saturated. Therefore, when Ta is added, the Ta content is set to 0.3% or less. On the other hand, the lower limit of the Ta content is not particularly limited, and may be 0%, but it is preferably set to 0.001% or more.

[0058] Zr: 0.3% or less Zr is an element that further improves strength and can be contained as necessary. Zr also has the effect of further improving SSC resistance. However, even if the Zr content exceeds 0.3%, the effect is saturated. Therefore, when Zr is added, the Zr content is set to 0.3% or less. On the other hand, the lower limit of the Zr content is not particularly limited and may be 0%, but it is preferably set to 0.0005% or more.

[0059] REM: 0.3% or less REM (rare earth metal) is an element that contributes to further improvement of sulfide stress cracking resistance through morphology control of sulfides, and can be contained as necessary. However, even if it is contained in an amount exceeding 0.3%, the effect is saturated, and an effect commensurate with the content cannot be expected. For this reason, when REM is added, the REM content is set to 0.3% or less. On the other hand, the lower limit of the REM content is not particularly limited, and may be 0%, but it is preferable to set it to 0.0005% or more. In addition, the REM in the present invention refers to scandium (Sc) with atomic number 21, yttrium (Y) with atomic number 39, and lanthanoids from lanthanum (La) with atomic number 57 to lutetium (Lu) with atomic number 71. The composition of the stainless steel seamless pipe of the present invention can contain at least one of the above REMs arbitrarily. The REM content in the present invention refers to the total content of the above elements.

[0060] Mg: 0.01% or less Mg is an element that further improves corrosion resistance and can be contained as necessary. However, even if it is contained in an amount exceeding 0.01%, the effect is saturated and no effect commensurate with the content can be expected. For this reason, when Mg is added, the Mg content is set to 0.01% or less. On the other hand, the lower limit of the Mg content is not particularly limited and may be 0%, but it is preferably set to 0.0005% or more.

[0061] Sb: 1.0% or less Sb is an element that further improves corrosion resistance and can be contained as necessary. However, even if it is contained in an amount exceeding 1.0%, the effect is saturated and no effect commensurate with the content can be expected. Therefore, when Sb is contained, the Sb content is set to 1.0% or less. On the other hand, the lower limit of the Sb content is not particularly limited and may be 0%, but it is preferably set to 0.001% or more.

[0062] [Organization] Next, the reasons for limiting the structure of the stainless steel seamless pipe of the present invention will be explained.

[0063] In a stainless steel seamless pipe according to one embodiment of the present invention, the martensite phase comprises 30% or more, the ferrite phase comprises 50% or less, and the retained austenite phase comprises 40% or less, by volume.

[0064] Martensite phase: 30% or more If the volume fraction of the martensite phase is less than 30%, the desired strength cannot be ensured. Therefore, the volume fraction of the martensite phase is set to 30% or more, preferably 40% or more, more preferably 45% or more, and even more preferably 50% or more. On the other hand, the upper limit of the volume fraction of the martensite phase is not particularly limited, but is preferably set to 90% or less, and more preferably set to 85% or less.

[0065] Ferrite phase: 50% or less By containing the ferrite phase, the progress of sulfide stress corrosion cracking and sulfide stress cracking can be suppressed, and excellent corrosion resistance can be obtained. However, if the volume fraction of the ferrite phase exceeds 50%, the desired strength cannot be ensured. Therefore, the volume fraction of the ferrite phase is set to 50% or less, preferably 40% or less, and more preferably 35% or less. On the other hand, the lower limit of the volume fraction of the ferrite phase is not particularly limited, but is preferably 10% or more, more preferably 15% or more, and even more preferably 20% or more.

[0066] Retained austenite phase: 40% or less The presence of the retained austenite phase improves ductility and low-temperature toughness. However, if a large amount of austenite phase, exceeding 40% by volume, is precipitated, the desired strength cannot be ensured. For this reason, the volume fraction of the retained austenite phase is set to 40% or less, preferably 30% or less, and more preferably 25% or less. On the other hand, the lower limit of the volume fraction of the retained austenite phase is not particularly limited, but is preferably 3% or more, and more preferably 5% or more.

[0067] Here, the volume fraction of each of the phases can be measured by the following method. First, a test piece for microstructure observation taken from a stainless steel seamless pipe is corroded with Villela's reagent (a mixture of 2 g picric acid, 10 ml hydrochloric acid, and 100 ml ethanol, respectively). Next, a scanning electron microscope (SEM) is used to capture the structure of the test piece for microstructure observation at a magnification of 1000 times to obtain an SEM image. The obtained SEM image is analyzed using image analysis software (ImageJ 1.52p, National Institute of Health) to calculate the structure fraction (area fraction (%)) of the ferrite phase. In the analysis, the SEM image is binarized, and the area with low brightness is regarded as the ferrite phase. The area fraction obtained by the above procedure is defined as the volume fraction (%) of the ferrite phase.

[0068] Next, the X-ray diffraction test piece taken from the stainless steel seamless pipe is ground and polished so that the cross section (C cross section) perpendicular to the pipe axis direction becomes the measurement surface, and the structural fraction of the retained austenite (γ) phase is measured using the X-ray diffraction method. Specifically, the volume fraction of the retained austenite phase is calculated from the integrated intensity of the (220) plane of austenite and the (211) plane of ferrite using the following formula. Vγ(%)=100 / (1+(IαRγ / IγRα)) Where: Vγ: volume fraction of retained austenite phase, Iα: integrated intensity of the (211) plane of ferrite, Iγ: Integrated intensity of the (220) plane of austenite, Rα: Theoretical crystallographic calculation value of α (34.15), Rγ: The theoretically calculated crystallographic value of γ (22.33).

[0069] The remainder other than the ferrite phase and the residual γ phase determined by the above measurement method is defined as the fraction of the martensite phase. The above observation methods for each structure are also described in detail in the examples below.

[0070] As described above, the structure of the stainless steel seamless pipe of the present invention is substantially composed of a martensite phase, a ferrite phase, and a retained austenite phase. In other words, the structure may contain other structures within a range that does not impair the effects of the present invention. Examples of the other structures include intermetallic compounds and inclusions.

[0071] In other words, the stainless steel seamless pipe in one embodiment of the present invention has a volume ratio of Fewer than 50% ferrite phase, and Contains 40% or less of retained austenite phase, the remainder being substantially martensite phase, and The microstructure may have a volume fraction of the martensite phase of 30% or more.

[0072] In another embodiment of the present invention, the stainless steel seamless pipe has a volume ratio of More than 30% martensite phase, Fewer than 50% ferrite phase, and The steel may have a structure consisting of 40% or less of a retained austenite phase.

[0073] In either case, however, it is acceptable for the above structure to contain unavoidable impurity phases.

[0074] Yield strength: 758MPa or more The stainless steel seamless pipe of the present invention has a yield strength of 758 MPa or more. The upper limit of the yield strength is not particularly limited, but it is preferably 1034 MPa or less. The yield strength can be measured by a tensile test. More specifically, it can be measured by the method described in the examples.

[0075] vE -10 :40J or more The stainless steel seamless pipe of the present invention has a Charpy absorbed energy vE -10 The Charpy absorbed energy vE -10 The higher the better, so the upper limit is not particularly limited, but may be, for example, 300 J or less, or 250 J or less. The Charpy absorbed energy can be measured by a Charpy impact test. More specifically, it can be measured by the method described in the examples.

[0076] The stainless steel seamless pipe of the present invention can be used for any purpose without any particular limitation, but is particularly suitable for use in oil wells. That is, the stainless steel seamless pipe in one embodiment of the present invention is a stainless steel seamless pipe for oil wells (high-strength stainless steel seamless pipe for oil wells).

[0077] [Manufacturing method] Next, a preferred method for producing the stainless steel seamless pipe of the present invention will be described.

[0078] The stainless steel seamless pipe of the present invention can be produced by forming a seamless steel pipe from a steel material and subjecting the seamless steel pipe to quenching and tempering treatment under specific conditions.

[0079] The steel material is not particularly limited and any material can be used. A billet is typically used as the steel material. The steel material can have the above-mentioned composition.

[0080] The method for producing the steel material is not particularly limited, and the steel material can be produced by any method. For example, molten steel having the above-mentioned composition can be produced by a melting method using a converter or the like, and then made into a steel material such as a billet by a method such as a continuous casting method or an ingot making-bloom rolling method.

[0081] [Pipe making] The above steel material is made into a seamless steel pipe. The method of making the pipe is not particularly limited, and any method can be used. The pipe is preferably made by hot working. When making the pipe by hot working, the steel material may be heated and then hot worked into a seamless steel pipe. The heating temperature in the heating is not particularly limited, but from the viewpoint of achieving both high levels of hot workability during pipe making and low-temperature toughness of the final product, it is preferably 1100 to 1350°C.

[0082] The method for processing the steel material into a seamless steel pipe is not particularly limited and any method can be used. For example, a seamless steel pipe can be obtained by either the Mannesmann plug mill method or the Mannesmann mandrel mill method.

[0083] When pipe-making is performed by hot working, a cooling treatment may be performed after pipe-making. The cooling treatment is not particularly limited and may be performed under any conditions. For example, it is preferable to cool the pipe to room temperature after hot working. The cooling rate in the cooling is not particularly limited and the pipe may be cooled at any rate. For example, the pipe may be cooled at a cooling rate equivalent to air cooling.

[0084] [Quenching-tempering treatment] Next, the obtained seamless steel pipe is subjected to a heat treatment consisting of a quenching treatment and a tempering treatment (quenching-tempering treatment) under specific conditions. The conditions of the quenching-tempering treatment will be described below.

[0085] Hardening treatment First, a seamless steel pipe is heated to a quenching temperature of 850 to 1150°C, and the heated seamless steel pipe is cooled to a cooling stop temperature of 50°C or lower at a cooling rate of 0.01°C / s or higher.

[0086] Quenching temperature: 850~1150℃ If the heating temperature (quenching temperature) in the quenching treatment is less than 850°C, reverse transformation from martensite to austenite does not occur, and transformation from austenite to martensite does not occur during cooling, making it impossible to ensure the desired strength. Therefore, the quenching temperature is set to 850°C or higher, preferably 900°C or higher. On the other hand, if the quenching temperature is higher than 1150°C, the crystal grains become coarse, resulting in deterioration of low-temperature toughness. Therefore, the quenching temperature is set to 1150°C or lower, preferably 1100°C or lower.

[0087] In the above quenching treatment, the seamless steel pipe may be heated to the quenching temperature, and then subjected to a soaking treatment in which the pipe is held at the quenching temperature. By performing the soaking treatment, the temperature of the seamless steel pipe in the wall thickness direction can be made uniform, and the variation in the material can be reduced. The time for which the pipe is held at the quenching temperature (soaking time) is not particularly limited, but is preferably 5 to 30 minutes.

[0088] Cooling rate: 0.01℃ / s or more If the cooling rate in the quenching treatment is less than 0.01°C / s, the desired structure cannot be obtained. Therefore, the cooling rate is set to 0.01°C / s or more, preferably 1.0°C / s or more, more preferably 5.0°C / s or more, and even more preferably 10.0°C / s or more. On the other hand, the upper limit of the cooling rate is not particularly limited, but it is preferably set to 100°C / s or less, more preferably 50°C / s or less, and even more preferably 30°C / s or less.

[0089] The cooling is not particularly limited and can be performed by any method. For example, the cooling is preferably performed by at least one of air cooling and water cooling, and more preferably by water cooling.

[0090] Cooling stop temperature: 50℃ or less If the cooling stop temperature is higher than 50°C, the desired structure cannot be obtained. In other words, if the cooling stop temperature is high, the transformation from austenite to martensite does not occur sufficiently, and the residual austenite fraction becomes excessive. Therefore, the cooling stop temperature in the above-mentioned quenching treatment is set to 50°C or less. On the other hand, the lower limit of the cooling stop temperature is not particularly limited, but may be, for example, 0°C or more. Here, the cooling stop temperature is the surface temperature of the seamless steel pipe.

[0091] ·Tempering treatment Next, the seamless steel pipe after the quenching treatment is subjected to a tempering treatment in which the pipe is heated to a tempering temperature of 500 to 650°C.

[0092] Tempering temperature: 500~650℃ If the tempering temperature is less than 500°C, the tempering effect is not sufficient, and as a result, the low-temperature toughness is deteriorated. Therefore, the tempering temperature is set to 500°C or higher, preferably 520°C or higher. On the other hand, if the tempering temperature is higher than 650°C, a large amount of intermetallic compounds is precipitated, and excellent low-temperature toughness cannot be obtained. Therefore, the tempering temperature is set to 650°C or lower, preferably 630°C or lower.

[0093] In the tempering treatment, the seamless steel pipe can be heated to the tempering temperature and then held at the tempering temperature. The time for which the pipe is held at the tempering temperature (holding time) is not particularly limited, but is preferably 5 minutes or more from the viewpoint of uniforming the temperature in the wall thickness direction and preventing material variations. On the other hand, the upper limit of the holding time is not particularly limited either, but is preferably 90 minutes or less.

[0094] After the tempering treatment, the material can be allowed to cool.

[0095] By carrying out the above quenching and tempering treatment, it is possible to obtain a stainless steel seamless pipe having a desired strength as well as excellent low-temperature toughness and corrosion resistance. EXAMPLES

[0096] The present invention will be further described below with reference to examples, but the present invention is not limited to the following examples.

[0097] First, seamless steel pipes were produced from steel materials having the chemical compositions shown in Tables 1 to 3 in the following procedure.

[0098] A steel material was cast using molten steel having the composition shown in Tables 1 to 3. The steel material was then heated and hot worked using a model seamless rolling mill to produce a seamless steel pipe having an outer diameter of 177.8 mm and a wall thickness of 16.0 mm, which was then air-cooled. The heating temperature of the steel material before hot working was 1250°C.

[0099] Next, the obtained seamless steel pipe was subjected to quenching and tempering treatment under the following conditions to obtain a stainless steel seamless pipe.

[0100] Hardening The obtained seamless steel pipe was subjected to quenching treatment under the conditions shown in Tables 4 to 6. That is, the seamless steel pipe was heated to the quenching temperature shown in Tables 4 to 6 and held at the quenching temperature for the soaking time shown in Tables 3 and 4. Then, it was cooled to a cooling stop temperature of 5°C at the cooling rate shown in Tables 4 to 6. The cooling was performed by water cooling.

[0101] Tempering Thereafter, the seamless steel pipe after cooling was heated to the tempering temperature shown in Tables 4 to 6 and held at the tempering temperature for the holding time shown in Tables 4 to 6. Thereafter, the seamless steel pipe was air-cooled (naturally cooled). The cooling rate in the air cooling was 0.04°C / s.

[0102] Test pieces were taken from the obtained stainless steel seamless pipes, and microstructural observation, tensile tests, Charpy impact tests, and corrosion resistance tests were carried out according to the following test methods.

[0103] (1) Tissue Observation A test piece for microstructure observation was taken from the obtained stainless steel seamless pipe so that the cross section including the pipe axis direction and the wall thickness direction was the observation surface. The obtained test piece for microstructure observation was corroded with Villela's reagent (a mixture of picric acid, hydrochloric acid and ethanol in the proportions of 2 g, 10 ml and 100 ml, respectively), and the structure was photographed at a magnification of 1000 times with a scanning electron microscope (SEM) to obtain an SEM image. The obtained SEM image was analyzed using image analysis software (ImageJ 1.52p, National Institute of Health), and the structure fraction (area fraction (%)) of the ferrite phase was calculated. In the above analysis, the SEM image was binarized, and the area with low brightness was regarded as the ferrite phase. The area fraction obtained by the above procedure was regarded as the volume fraction (%) of the ferrite phase.

[0104] In addition, test pieces for X-ray diffraction were taken from the obtained stainless steel seamless pipe, ground and polished so that the cross section (C cross section) perpendicular to the pipe axis direction became the measurement surface, and the structural fraction of the retained austenite (γ) phase was measured using the X-ray diffraction method. Specifically, the volume fraction of the retained austenite phase was calculated from the integrated intensity of the (220) plane of austenite and the (211) plane of ferrite using the following formula. Vγ(%)=100 / (1+(IαRγ / IγRα)) Where: Vγ: volume fraction of retained austenite phase, Iα: integrated intensity of the (211) plane of ferrite, Iγ: Integrated intensity of the (220) plane of austenite, Rα: Theoretical crystallographic calculation value of α (34.15), Rγ: The theoretically calculated crystallographic value of γ (22.33).

[0105] The volume fractions of the phases obtained by the above procedures are shown in Tables 4 to 6. Note that the symbols M, F, and γ for the structures shown in Tables 4 to 6 respectively represent the following phases. M: Martensite phase F: Ferrite phase γ: Retained austenite phase

[0106] (2) Tensile test From the obtained stainless steel seamless pipe, an arc-shaped tensile test piece was taken in accordance with the API (American Petroleum Institute)-5CT standard so that the pipe axis direction was the tensile direction, and a tensile test was carried out to determine the yield strength (YS). Here, a specimen with a yield strength YS of 758 MPa or more was deemed to be high strength and passed, and a specimen with a yield strength YS of less than 758 MPa was deemed to have failed.

[0107] (3) Charpy impact test In order to evaluate the low temperature toughness, a Charpy impact test was carried out according to the following procedure.

[0108] First, V-notch test pieces (10 mm thick) were taken from the obtained stainless steel seamless pipes in accordance with the provisions of ASTM E23, in which the longitudinal direction of the test piece was perpendicular to the pipe axis and the notch was on a plane perpendicular to the pipe axis. Using the test pieces, a Charpy impact test was carried out at a test temperature of -10°C. In the above test, three test pieces were taken from one stainless steel seamless pipe, and the absorbed energy was measured for each test piece. The minimum absorbed energy of the three test pieces was defined as the Charpy absorbed energy vE at -10°C. -10 vE -10 The test was deemed to have passed if the value was 40J or more.

[0109] (4) Carbon dioxide corrosion resistance test In order to evaluate the carbon dioxide gas corrosion resistance at high temperatures, the following test was carried out.

[0110] A corrosion test piece having a thickness of 3 mm, width of 30 mm, and length of 40 mm was prepared by machining from the obtained stainless steel seamless steel pipe. A corrosion test was performed using the corrosion test piece, and the corrosion rate as an index of carbon dioxide corrosion resistance was measured. The corrosion test was performed by immersing the corrosion test piece in a test liquid: 20 mass% NaCl aqueous solution (liquid temperature: 200°C, CO2 gas atmosphere at 30 atm) held in an autoclave for a period of 14 days (336 hours). The weight of the corrosion test piece after the corrosion test was measured, and the weight of the test piece before the corrosion test, which was measured in advance, was subtracted to obtain the weight loss due to the corrosion test. Next, the weight loss was divided by the surface area of ​​the test piece used and the immersion period to obtain the weight loss per unit time and unit area. The weight loss per unit time and unit area was then converted to the corrosion thickness per unit time and unit area by dividing the weight loss per unit time and unit area by the density of the steel. The corrosion thickness per unit time and unit area (mm / y) obtained in this way was taken as the corrosion rate in carbon dioxide. Here, a corrosion rate of 0.127 mm / y or less was considered to be acceptable, and a corrosion rate of more than 0.127 mm / y was considered to be unacceptable.

[0111] (5) SSC resistance test To evaluate the SSC resistance at low temperatures, the following tests were carried out.

[0112] From the obtained stainless steel seamless pipe, C-shaped test pieces were machined in accordance with NACE TM0177 Method C, and SSC resistance tests were carried out. Note that no grinding or polishing was performed on the curved surfaces corresponding to the inner and outer surfaces of the steel pipe.

[0113] The SSC resistance test was performed by immersing a C-shaped test piece conforming to NACE TM0177 Method C in a 0.165 mass% NaCl aqueous solution (liquid temperature: 7°C, CO2 gas at 0.995 atm, H2S atmosphere at 0.005 atm) adjusted to pH 3.0 by adding acetic acid and sodium acetate, immersion time was 720 hours, and loading stress was 100% of the yield stress. Here, a specimen without cracks was deemed to pass, and a specimen with cracks was deemed to fail, and in Tables 4 to 6, a pass was indicated by "1" and a fail was indicated by "2".

[0114] (6) Corrosion test in acid environment To evaluate the corrosion resistance in an acid environment, the following tests were carried out.

[0115] First, a rectangular parallelepiped test piece was created by machining from the obtained stainless steel seamless steel pipe. The dimensions of the test piece were 50 mm in the longitudinal direction of the steel pipe, 3 mm in the thickness direction of the steel pipe, and 25 mm in width. After measuring the weight of the test piece, the test piece was immersed in a 15% by mass hydrochloric acid solution heated to 80 ° C for 40 minutes to perform a corrosion test. The weight of the test piece after the corrosion test was measured, and the weight of the test piece before the corrosion test was subtracted to obtain the weight loss due to the corrosion test. Next, the weight loss was divided by the surface area of ​​the test piece used and the immersion time in the corrosion test to obtain the weight loss per unit time and unit area. Then, the weight loss per unit time and unit area was converted into the corrosion thickness per unit time and unit area by dividing the weight loss per unit time and unit area by the density of the steel. The corrosion thickness per unit time and unit area (mm / y) obtained in this way was taken as the corrosion rate in the acid environment. Here, a corrosion rate of 600 mm / y or less was deemed to be acceptable, and a corrosion rate of more than 600 mm / y was deemed to be unacceptable.

[0116] (7) Hot workability Furthermore, the following evaluation was performed to evaluate the hot workability of the obtained stainless steel seamless pipe. The flaw depth on the surface of the test piece of the SSC resistance test that corresponds to the outer surface of the steel pipe was measured by ultrasonic flaw detection. Based on the maximum flaw depth measured, the hot workability was evaluated into the following three levels. 1: Maximum scratch depth is 0.1mm or less 2: Maximum scratch depth is over 0.1mm and 0.2mm or less 3: Maximum scratch depth is over 0.2 mm

[0117] The results obtained are shown in Tables 4 to 6. As can be seen from the results shown in Tables 4 to 6, all of the stainless steel seamless pipes satisfying the conditions of the present invention had high strength, with a yield strength of 758 MPa (110 ksi) or more, as well as excellent low-temperature toughness and corrosion resistance. In particular, the corrosion resistance was excellent in all of "resistance to carbon dioxide corrosion at high temperatures," "resistance to SSC at low temperatures," and "corrosion resistance in acid environments." Therefore, the stainless steel seamless pipe of the present invention can be used extremely suitably for various applications, including steel pipes for oil wells.

[0118] Furthermore, in the inventive examples in which the Ca content was more than 0.010%, the maximum flaw depth was 0.1 mm or less. This result indicates that the hot workability is remarkably excellent, particularly when the Ca content is more than 0.010%. Therefore, it can be said that if the Ca content is more than 0.010%, the SSC resistance at low temperatures is further improved.

[0119] [Table 1]

[0120] [Table 2]

[0121] [Table 3]

[0122] [Table 4]

[0123] [Table 5]

[0124]

Table 6

Claims

1. In mass percent, C: 0.06% or less, Si: 1.0% or less, Mn: 0.01% or more and 1.0% or less, P: 0.05% or less, S: 0.005% or less, Cr: 15.2% or more and 18.0% or less, Mo: 1.5% or more and 4.3% or less, Cu: 1.2% or more and 3.5% or less, Ni: 3.5% or more and 5.2% or less, V: 0.03% or more and 0.5% or less, Al: 0.10% or less, N: 0.10% or less, O: 0.010% or less, Sn: 0.001% or more and 1.000% or less Co: 0.01% or more and 1.00% or less, and Ca: 0.001% or more and 0.030% or less; The balance is Fe and unavoidable impurities, In terms of volume ratio, Martensite phase is 30% or more, Ferrite phase is 50% or less, and The retained austenite phase is 40% or less, Yield strength is 758 MPa or more, Charpy absorbed energy vE at -10℃ -10 Stainless steel seamless pipe with a hardness of 40J or more.

2. The composition of the components is, in mass%, Nb: 0.07% or less, Ti: 0.2% or less, B: 0.01% or less, Ta: 0.3% or less, Zr: 0.3% or less, REM: 0.3% or less, and Mg: 0.01% or less The stainless steel seamless pipe according to claim 1, further comprising at least one selected from the group consisting of:

3. In terms of volume ratio, Martensite phase is 50% or more, Ferrite phase is 50% or less, and The retained austenite phase is 25% or less, 3. The stainless steel seamless pipe according to claim 1 or 2, having a yield strength of 862 MPa or more.

4. A seamless steel pipe is produced from a steel material having the composition according to claim 1 or 2, The seamless steel pipe is heated to a quenching temperature of 850 to 1150°C, The seamless steel pipe after the heating is cooled at a cooling rate of 0.01° C. / s or more to a cooling stop temperature of 50° C. or less, The seamless steel pipe after cooling is heated to a tempering temperature of 500 to 650°C, In terms of volume ratio, Martensite phase is 30% or more, Ferrite phase is 50% or less, and The retained austenite phase is 40% or less, Yield strength is 758 MPa or more, Charpy absorbed energy vE at -10℃ -10 A method for manufacturing a stainless steel seamless pipe, comprising the steps of: manufacturing a stainless steel seamless pipe having a hardness of 40 J or more.

5. In terms of volume ratio, Martensite phase is 50% or more, Ferrite phase is 50% or less, and The retained austenite phase is 25% or less, The method for producing a stainless steel seamless pipe according to claim 4, wherein the yield strength is 862 MPa or more.

Citation Information

Patent Citations

  • Seamless steel pipe

    JP2021161503A

  • JPP7226675B

  • JPP7409569B

  • Stainless steel for oil wells and stainless steel pipe for oil wells

    WO2013146046A1

  • Stainless steel seamless tube for use in oil well and manufacturing process therefor

    WO2014112353A1